Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.43 Laplace transform of cosax\cos ax.

Prop. 6.42 can sometimes provide an easy way to calculate the Laplace transform of a function.

Example.

To deduce the Laplace transform of cosax\cos ax from the Laplace transform of sinax\sin ax.

Solution. Setting f(x)=sinaxf(x)=\sin ax, we have f(x)=acosaxf^{\prime}(x)={a\cos ax} in the previous theorem. Thus, for s>as>a the Laplace transform of acosaxa\cos ax equals

-f(0)+sas2+a2=ass2+a2.{-f(0)+s\frac{a}{s^{2}+a^{2}}}\,{=\frac{as}{s^{2}+a^{2}}.}

It follows that:

0e-sxcosaxdx=ss2+a2  for s>as>a.\int_{0}^{\infty}e^{-sx}\cos ax\,dx=\,{\frac{s}{s^{2}+a^{2}}}\mbox{\; for $s>a% $}.